Dopaminergic denervation severity depends on COMT Val158Met polymorphism in Parkinson's disease. Issue 5 (May 2015) - Muellner, Julia; Gharrad, Iman; Habert, Marie-Odile; Kas, Aurélie; Martini, Jean-Baptiste; Cormier-Dequaire, Florence; Tahiri, Khadija; Vidailhet, Marie; Meier, Niklaus; Brice, Alexis; Schuepbach, Michael; Mallet, Alain; et al.
Abstract Background Catecholamine-O-methyl-tranferase (COMT) initiates dopamine degradation. Its activity is mainly determined by a single nucleotide polymorphism in the COMT gene (Val158Met, rs4680) separating high (Val/Val, COMTHH), intermediate (Val/Met, COMTHL) and low metabolizers (Met/Met, COMTLL). We investigated dopaminergic denervation in the striatum in PD patients according to COMT rs4680 genotype. Methods Patients with idiopathic PD were assessed for motor severity (UPDRS-III rating scale in OFF-state), dopaminergic denervation using [123I]-FP-CIT SPECT imaging, and genotyped for the COMT rs4680 enzyme. [123I]-FP-CIT binding potential (BP) for each voxel was defined by the ratio of tracer-binding in the region of interest (striatum, caudate nucleus and putamen) to that in a region of non-specific activity. Genotyping was performed using TaqMan® SNP genotyping assay. We used a regression model to evaluate the effect of COMT genotype on the BP in the striatum and its sub-regions. Results Genotype distribution was: 11 (27.5%) COMTHH, 26 (65%) COMTHL and 3 (7.5%) COMTLL. There were no significant differences in disease severity, treatments, or motor scores between genotypes. When adjusted to clinical severity, gender and age, low and intermediate metabolizers showed significantly higher rates of striatal denervation (COMTHL+LL BP = 1.32 ± 0.04) than high metabolizers (COMTHH, BP = 1.6 ± 0.08; F(1.34) = 9.0, p = 0.005). Striatal sub-regions showed similar results. BP and UPDRS-III motor scores (r = 0.44, p = 0.04) (p < 0.001) were highly correlated. There was a gender effect, but no gender–genotype interaction. Conclusions Striatal denervation differs according to COMT-Val158Met polymorphism. COMT activity may play a role as a compensatory mechanism in PD motor symptoms.